(untitled) (Economics, Entrepreneurship and Management Research, 2025)
The global economy has been in a serious crisis for several years, which has deepened and accelerated in 2022 and 2023, so that a large number of countries are threatened with an economic recession with the possibility of transitioning into stagflation. The rise in energy, food, and other input prices has caused high inflation rates, both in developed and developing countries, regardless of their geographical location. The general impression is that some central banks that apply inflation targeting regime have reacted with delay, considering the rise in prices as a passing phenomenon of a temporary nature. Developing countries are in the most difficult situation and will have to borrow under unfavorable conditions to avoid a recession in their economies. The paper analyzes the possibilities and limitations of monetary and fiscal policy in preventing inflation and maintaining positive economic growth rates, with the aim of reducing unemployment, preventing a debt crisis, and reducing the standard of living of the population.